ChemInform Abstract: Crystal Structure and Magnetic Properties of FeSeO3F — Alternating Antiferromagnetic S= 5/2 Chains. Issue 26 (1st July 2014) - Hu, Shichao; Johnsson, Mats; Law, Joseph M.; Bettis, Jerry L. Jr.; Whangbo, Myung‐Hwan; Kremer, Reinhard K.
Abstract Single crystals of the new title compound are hydrothermally prepared from an aqueous mixture of FeF3 and SeO2 (autoclave, 230 °C, 3 d).